CORRELATION BETWEEN EMOTIONAL INTELLIGENCE AND ANXIETY OF APPLIED MIDWIFERY BACHELOR STUDENTS WHO ARE COMPILING THEIR THESIS - Sri Puji Lestari; Achmat Syaifudin; Bachtiar Kusuma Dewa; Mona Saparwati (Universitas Karya Husada Semarang, 2024)
Background: The thesis is a final project that is generally achieved in the final study. Students consider the thesis to be a difficult thing to work because of feelings of anxiety when students are in the process of working on a thesis. pressure from people around who demanded students to complete their thesis creation. Anxiety that causes feelings of pressure to students. Objective: how is the relationship between emotional intelligence and applied midwifery undergraduate students who are writing a thesis at Karya Husada University Samarang Method : non-experimental quantitative research is correlational analytic and research type is correlational analytic in research using proportional sampling The number of samples in this study were respondents 24 respondents, 12 respondents from class A and 12 respondents from class B using the DASS 42 anxiety questionnaire and the Emotional Intelligence Questionnaire, researchers adopted research from Agustina 2007, used the chi-square analysis Results: Respondents with 22 years of age were 9 (37.5%), respondents with moderate emotional intelligence were 15 respondents (62.5% ), Based on the Chi-square test, a P value of 0.03 was obtained. Conclusion: there is a relationship between emotional intelligence and applied midwifery undergraduate students who are writing their thesis at Universitas Karya Husada Semarang.